Flora of the Regional Reserve “Tavolzhansky” (Tyumen Region) - Kapitonova, O.A. (Acta Biologica Sibirica, 2019)
Based on research materials in 2016 and 2018, a list of the flora of vascular plants of the regional natural reserve "Tavolzhansky" (Sladkovsky district, Tyumen region), which is a part of the wetland of international importance "Lakes of Tobol-Ishim forest-steppe", was updated. The revealed flora includes 228 species of vascular plants from 154 genera and 47 families. In this flora, 101 species are new to the territory of reserve, and 37 species are new to the Sladkovsky district. The conspectus of the identified flora with indicating the abundance and occurrence of species is given. The growth of 8 plant species protected in the Tyumen region was detected within the studied territory, and the condition of their populations was assessed. It was proposed to expand the territory of the reserve with include the entire water area of the lake Solyonoje, within is located the Tavolzhan island. This will contribute to the preservation of populations of not only protected plant species, but also waterfowl and near-water birds.